2013
DOI: 10.1002/adma.201303567
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelectric Domain Wall Injection

Abstract: Ferroelectric domain wall injection has been demonstrated by engineering of the local electric field, using focused ion beam milled defects in thin single crystal lamellae of KTiOPO4 (KTP). The electric field distribution (top) displays localized field hot-spots, which correlate with nucleation events (bottom). Designed local field variations can also dictate subsequent domain wall mobility, demonstrating a new paradigm in ferroelectric domain wall control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
63
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(65 citation statements)
references
References 45 publications
2
63
0
Order By: Relevance
“…Exotic domain-wall phenomena are observed in archetypal ferroelectrics, such as BaTiO 3 (refs 12,13), PbZr 0.2 Ti 0.8 O 3 (refs 7,14,15) and LiNbO 3 (ref. 16), where metastable charged domain walls can be induced by, for example, electric fields 17 . Additional degrees of freedom arise in so-called improper ferroelectrics, where the polarization emerges due to the coupling to a primary structural or magnetic order parameter.…”
mentioning
confidence: 99%
“…Exotic domain-wall phenomena are observed in archetypal ferroelectrics, such as BaTiO 3 (refs 12,13), PbZr 0.2 Ti 0.8 O 3 (refs 7,14,15) and LiNbO 3 (ref. 16), where metastable charged domain walls can be induced by, for example, electric fields 17 . Additional degrees of freedom arise in so-called improper ferroelectrics, where the polarization emerges due to the coupling to a primary structural or magnetic order parameter.…”
mentioning
confidence: 99%
“…It has recently become evident that ferroelectric domain walls can possess diverse functional characteristics that are completely different from the domains that they delineate: they can be conducting 2 , or even superconducting 3 , when the domains themselves are insulating. Moreover, they can be moved, injected and annihilated by external electric fields 4 , so that their potential use in 'active' two-dimensional electronic devices is overwhelmingly clear. Hong and colleagues' imaging technique rapidly locates ferroelectric domain walls and could therefore be invaluable in supporting the quest for "domain wall nanoelectronics" 5 .…”
Section: J Marty Gregg and Amit Kumarmentioning
confidence: 99%
“…33. A platinized MgO substrate was used to create co-planar electrodes by FIB milling, leaving a $2 lm wide interelectrode gap.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…In previous work, Whyte et al 33 demonstrated that lowpermittivity air holes, milled into a ferroelectric of higher permittivity, could create local regions of both field enhancement and denudation. Regions of field enhancement were previously found to act as nucleation sites during switching, while low field regions could cause domain wall pinning.…”
Section: B Controlled Domain Wall Injection Using Milled Holes In Ktmentioning
confidence: 99%
See 1 more Smart Citation